Pelaksanaan Pembelajaran Tahfidz Di TPA At-Taqwa Jorong Koto Hilalang, Nagari Balingka, Kabupaten Agam - Putri Helsya, Alma Oktari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
The purpose of this study was to find out how the implementation of Al-Quran learning in TPA AT-Taqwa Jorong kotohilalang Balingka Kab. religion. Memorizing the Al-Quran is one of the important subjects at TPA AT-Taqwa, where at TPA At-Taqwa itself targets students to be able to memorize juz 30 before completing the Al-Quran. Of course this does not always go smoothly, there will be obstacles that come to teachers, parents, and students, considering the ability of each student to memorize the Al-Quran is different, some are fast and some are slow. In terms of reading and memorizing the Koran is certainly not an ordinary and easy thing. Because one way to read and memorize the Al-Quran is correct by knowing and mastering the science of recitation as part of the ulumul Qur'an that needs to be learned, but there are still many problems with children reading the Qur'an. First, they can't distinguish between letters. The second is not in accordance with the rules of recitation. The three children have not been able to understand well the material presented by the teacher.